Integrated bioinformatics and molecular docking analysis reveal potential hub genes and targeted therapeutics in sepsis-associated acute lung injury - Chen, Qiongyan; Mao, Yifeng; Cai, Shangwen; Zhang, Xijiang; Zeng, Chenghao; Chen, Qingqing; Zheng, Cheng (Frontiers in Immunology, 2025)
BackgroundSepsis-associated acute lung injury (SA-ALI) is a severe complication of sepsis with high mortality. This study aimed to identify key diagnostic genes and potential therapeutic drugs for SA-ALI.MethodsTranscriptomic data from GSE10474 and GSE32707 were integrated for differential expression and WGCNA analysis. Hub genes were screened using PPI network construction and three machine learning algorithms, and validated by Western blot. Functional enrichment, immune infiltration, and drug prediction (DSigDB) were performed, followed by molecular docking.ResultsSix hub genes (PGM3, GDF15, GART, GFOD2, E2F2, ATP1B2) were identified and validated with elevated expression in SA-ALI. These genes were enriched in inflammation, immune regulation, oxidative stress, and tissue remodeling pathways, and showed significant correlations with specific immune cell subsets. Five candidate small molecules were predicted; molecular docking revealed Celastrol had the strongest binding to all six proteins, particularly GDF15 (-9.988 kcal/mol), while Thiostrepton showed strong binding to PGM3, GFOD2, and GDF15.ConclusionSix diagnostic hub genes and two priority candidate drugs, Celastrol and Thiostrepton, were identified for SA-ALI, providing potential biomarkers and therapeutic targets.